Multicultural Values in Learning as a Form of Adaptation to Multiethnic Society - Santie, Yoseph D. A.; Fathimah, Siti; Suarjana, I Wayan Gede; Sasea, Sanita C. (Technium Social Sciences Journal, 2023)
This research aims to examine students’ understanding of multicultural values obtained from schools in familiarizing students to practice multicultural values in social life, this research uses qualitative methods that are studied descriptively, this research was conducted at SMA Negeri 3 Tondano. The result of this research is that students’ understanding of multiculturalism values is very diverse. The values understood by students include the value of tolerance, mutual respect, respect for other cultures, avoiding primordialism that leads to ethnocentrism, unity, togetherness, cooperation and solidarity. The application of multiculturalism values in SMA Negeri 03 Tondano is going well, where teachers often apply the group discussion method in the implementation of the teaching and learning process, through this group discussion the teacher anticipates to divide members according to differences in diverse cultural backgrounds, through teaching material Culture in Anthropology material, Social Groups in Sociology material, the teacher provides stimulation in the material in the form of active group discussions and directly applies the core of the material presented in accordance with the learning objectives. Thus, teachers provide real examples to students regarding how to apply these multicultural values in social life, and create meaningful learning situations for students.